List of grrnhouse gas emissions by carbon equivalent methods in coffee’s culture - Oliveira Junior, Geraldo Gomes de; SILVA, ADRIANO BORTOLOTTI DA; Mantovani, José Ricardo; Miranda, José Messias; Florentino, Ligiane Aparecida (Coffee Science - ISSN 1984-3909, 2015)
Coffee culture is one of the main activities of the South of Minas Gerais State. Gases emissions related to greenhouse effect (GHG) in coffee production occur from different sources. Inventory of GHG emissions is essential for a coffee farm to assess how their activities impact the environment in relation to these emissions. The aim of this study was to identify and quantify the major sources GHGs emissions in the coffee culture in the South of Minas Gerais State, and converts them into carbon equivalent per hectare (tCO2eq ha-1). The inventory was carried out using parameters of the GHG Protocol, Ministry of Science and Technology and IPCC data. The inventory showed GHG emissions generated in coffee production to 2.13 tCO2eq ha-1, whereas nitrogen fertilizers issued 1.01 tCO2eq ha-1(47,5%), lime issued 0.65 tCO2eq ha-1(30,8%), fossil fuels contributed with 0.35 tCO2eq ha-1 (16.9%), residential GLP issued 0.049 tCO2eq ha-1 (2,3%) and electric power contributed with 0.050 tCO2eq ha-1 (2,4%).